Sons of the Gods, Children of Earth Ideology and Literary Form in Ancient Greece - Rose, Peter W. 1936- (Ithaca, NY Cornell University Press, 2019)
Frontmatter --Contents --Preface --Introduction: Marxism and the Classics --1. How Conservative Is the Iliad? --2. Ambivalence and Identity in the Odyssey --3. Historicizing Pindar: Pythian 10 --4. Aeschylus' Oresteia: Dialectical Inheritance --5. Sophokles' Philoktetes and the Teachings of the Sophists: A Counteroffensive --6. Plato's Solution to the Ideological Crisis of the Greek Aristocracy --Afterword --References --Index
In English
Keywords: Greek literature -- History and criticism; Literary Form -- History -- To 1500; Politics and literature -- Greece; Marxist criticism; LITERARY CRITICISM / Ancient & Classical; Greek literature; Literary Form; Politics and government; Politics and literature; Greece; Criticism, interpretation, etc; History; Greece -- Politics and government